Library Automation and Software Packages for Libraries: A Study of the Library Automation Software Libsys7: Exploring Library Automation Software and RFID Technology in Libraries (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study has been taken in terms of its usefulness regarding the need of RFID (Radio Frequency Identification Technology) in libraries, its functions, installation and control etc. The main aim behind this analysis is to know about the latest technology and tools used for LA (Library Automation) and how it is applicable in housekeeping operations of the library activities. This paper presents concept of LA, definitions, efforts for LA and its systematically historical development, why LA necessary? To find out the areas where LA is applicable, LA software Libsys7 integrated with RFID technology at Dhanvantri Library, University of Jammu and describes the name of the current automation software packages available for libraries and in use in the market.